2013
DOI: 10.1016/j.neuroimage.2012.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Improved in vivo diffusion tensor imaging of human cervical spinal cord

Abstract: We describe a cardiac gated high in-plane resolution axial human cervical spinal cord diffusion tensor imaging (DTI) protocol. Multiple steps were taken to optimize both image acquisition and image processing. The former includes slice-by-slice cardiac triggering and individually tiltable slices. The latter includes (i) iterative 2D retrospective motion correction, (ii) image intensity outlier detection to minimize the influence of physiological noise, (iii) a non-linear DTI estimation procedure incorporating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 86 publications
2
66
4
Order By: Relevance
“…The trend for our DTI indices is consistent with previous findings (Vedantam et al, 2013;Wheeler-Kingshott et al, 2002a;Xu et al, 2013) and in agreement with tract-specific measures in the lateral and dorsal columns of the cervical cord WM (Smith et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The trend for our DTI indices is consistent with previous findings (Vedantam et al, 2013;Wheeler-Kingshott et al, 2002a;Xu et al, 2013) and in agreement with tract-specific measures in the lateral and dorsal columns of the cervical cord WM (Smith et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…1. Although in the literature registration transformations have been estimated directly for the DW volumes (Mohammadi et al, 2013;Xu et al, 2013) or at least for the mean DW volume (Cohen-Adad et al, 2011), it should be noted that in such studies the diffusion weighting strength was much lower than here: the maximum b-value was equal to 500 s mm −2 in Mohammadi et al (2013), to 800 s mm −2 in Xu et al (2013) and to 1000 s mm −2 in Cohen- Adad et al (2011). Our procedure implicitly assumes that negligible motion has occurred during the acquisition of the DW volumes between two subsequent b = 0 ones, and visual inspection of the uncorrected and corrected data proved that this hypothesis described our data reasonably well.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies would be needed specifically in women in relation to menopause. With the development of MRI technologies and the continuous optimization of the parameters [33], DTI is increasingly being used in various chronic spinal cord diseases, especially in cervical spondylotic myelopathy (CSM) and injuries. Previous studies [34][35][36] about CSM offer a comparative analysis between the CSC DTI parameters according to age and lesion site, but without considering the combined influence of age and segments.…”
Section: Discussionmentioning
confidence: 99%
“…Myelopathy is represented radiographically with increased cord signal on T2-weighted MRI and a decreased signal on T1-weighted imaging [28] . Diffusion tensor imaging (DTI) improves pathologic specificity by measuring directional diffusivities, which quantify water diffusion parallel and perpendicular to the white matter tracts [16,29] . A recent study of the role of DTI in cervical spondylotic myelopathy suggested that DTI may elucidate pathology of the spinal cord before the development of T2 hyperintensity imaging and thus may be a superior imaging modality in the future [13] .…”
Section: Static Mechanical Factorsmentioning
confidence: 99%
“…Whilst the aetiology of cervical myelopathy is thought to be multifactorial including contributions from age-related degeneration, mechanical stress and biochemical factors, a genetic predisposition has been revisited, due to recent evidence of familial clustering in population studies [12] . Despite advances in the surgical management of cervical myelopathy in addition to earlier diagnosis facilitated by advances in diffusion tensor magnetic resonance imaging (MRI) and kinetic MRI, a significant proportion of patients suffer residual neurological sequele as a consequence of irreversible cord injury [13][14][15][16][17] . Thus, implementation of neuro-protective interventions as an adjunct to surgical decompression may optimise patient outcomes for cervical myelopathy.…”
Section: Introductionmentioning
confidence: 99%